Resonance Suppression of a Maglev Inertially Stabilized Platform Based on an Improved Recursive Least Square Algorithm - Shi, Wanfa; Liu, Kun; Wei, Jingbo (Applied sciences, 2022)
Mechanical resonance occurs during the operation of a maglev inertially stabilized platform (MISP). The MISP is driven by the motor gear and the gear clearance changes during commutation, which makes the resonance frequency variable. Conventional notch filters with constant parameters are not ideal for variable frequency resonance suppression. In this study, the forgetting factor in the recursive least squares (RLS) algorithm was improved to estimate the resonance frequency online. By adjusting the frequency parameters of the notch filter, the proposed measures can effectively suppress the variable frequency resonance in a dual-stage MISP system. Finally, a simulation example is presented to validate the arguments in this study.